Does mass drug administration affect Schistosoma mansoni infection trends in West Dembia district, Northwest Ethiopia? - Ayalew Jejaw Zeleke; Ayenew Addisu; Abebe Genetu Bayih; Hannock Tweya; Collins Timire; Werku Techilo; Edward Mberu Kamau; Florian Vogt; Kristien Verdonck (Journal of Infection in Developing Countries)
Introduction: Schistosomiasis is one of the Neglected Tropical Diseases in Ethiopia. Since 2015, yearly school-based mass drug administration (MDA) using praziquantel has become the major control strategy. This study aimed to assess trends of Schistosoma mansoni infection in a high-endemic area in Northwest Ethiopia.